THE INFLUENCE OF RETURN ON ASSETS, QUICK RATIO, FIRM SIZE, AND ASSET STRUCTURE ON CAPITAL STRUCTURE: AN EMPIRICAL STUDY OF RETAIL SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020–2024 - Imelia Aprilyanti; Astrid Dita Meirina Hakim (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the effect of return on assets, quick ratio, firm size, and asset structure on capital structure in retail sub-sector companies listed on the Indonesia Stock Exchange. Using panel data regression analysis, the findings indicate that return on assets has a positive and significant influence on capital structure, suggesting that higher profitability enhances the firm’s ability to optimize its financial structure. The quick ratio shows a negative and significant impact, reflecting that higher liquidity reduces the need for external debt. Firm size also contributes positively, implying that larger firms have broader access to funding sources. Meanwhile, asset structure demonstrates no significant relationship with capital structure, highlighting that retail companies are less dependent on fixed assets in financing decisions. These results offer insights for managers and investors in understanding the financial behavior of retail firms during the transition toward digital business environments.